N-Type organic semiconducting polymers: stability limitations, design considerations and applications. Issue 26 (15th June 2021) - Griggs, Sophie; Marks, Adam; Bristow, Helen; McCulloch, Iain
Abstract : This review summarises high performing n-type polymers for use in organic thin film transistors, organic electrochemical transistors and organic thermoelectric devices with a focus on stability issues arising in these electron transporting materials. Abstract : This review outlines the design strategies which aim to develop high performing n-type materials in the fields of organic thin film transistors (OTFT), organic electrochemical transistors (OECT) and organic thermoelectrics (OTE). Figures of merit for each application and the limitations in obtaining these are set out, and the challenges with achieving consistent and comparable measurements are addressed. We present a thorough discussion of the limitations of n-type materials, particularly their ambient operational instability, and suggest synthetic methods to overcome these. This instability originates from the oxidation of the negative polaron of the organic semiconductor (OSC) by water and oxygen, the potentials of which commonly fall within the electrochemical window of n-type OSCs, and consequently require a LUMO level deeper than ∼−4 eV for a material with ambient stability. Recent high performing n-type materials are detailed for each application and their design principles are discussed to explain how synthetic modifications can enhance performance. This can be achieved through a number of strategies, including utilising an electron deficient acceptor–acceptor backbone repeat unit motif, introducing electron-withdrawing groups or heteroatoms, rigidification and planarisation of the polymer backbone and through increasing the conjugation length. By studying the fundamental synthetic design principles which have been employed to date, this review highlights a path to the development of promising polymers for n-type OSC applications in the future.